2012
DOI: 10.1016/j.jff.2011.11.001
|View full text |Cite
|
Sign up to set email alerts
|

Bioaccessibility and antioxidant potential of millet grain phenolics as affected by simulated in vitro digestion and microbial fermentation

Abstract: DPPH EPRHydroxyl radicals ORAC Short chain fatty acids A B S T R A C T Dehulled and cooked grains of five millet varieties (kodo, finger, proso, foxtail and pearl) were subjected to in vitro enzymatic digestion and microbial fermentation under physiological conditions in order to determine the bioaccessibility of their phenolic compounds.Extracts recovered as supernatants from enzymatic digestion and microbial fermentation were employed for the determination of their total phenolic content (TPC) and total f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
125
1
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 271 publications
(142 citation statements)
references
References 43 publications
14
125
1
2
Order By: Relevance
“…Different lowercase letters marked on the columns for each fraction of buckwheat enriched wheat breads indicate significant differences amongst the means (p < 0.05) soluble fraction of the reference white wheat bread was comparable to the content of these compounds in the dark wheat bread (with high difference of these compounds before digestion). This is in accordance with the results achieved by other scientists (Gawlik-Dziki et al 2009;Chandrasekara and Shahidi 2012). LiyanaPathirana and Shahidi (2005) also demonstrated that simulated gastrointestinal conditions significantly increased the TPC of extracts obtained from wheat whole grains and their flour, germ and bran fractions.…”
Section: Total Phenolic Content (Tpc) Before and After Digestionsupporting
confidence: 91%
See 2 more Smart Citations
“…Different lowercase letters marked on the columns for each fraction of buckwheat enriched wheat breads indicate significant differences amongst the means (p < 0.05) soluble fraction of the reference white wheat bread was comparable to the content of these compounds in the dark wheat bread (with high difference of these compounds before digestion). This is in accordance with the results achieved by other scientists (Gawlik-Dziki et al 2009;Chandrasekara and Shahidi 2012). LiyanaPathirana and Shahidi (2005) also demonstrated that simulated gastrointestinal conditions significantly increased the TPC of extracts obtained from wheat whole grains and their flour, germ and bran fractions.…”
Section: Total Phenolic Content (Tpc) Before and After Digestionsupporting
confidence: 91%
“…Nonetheless, food products have difficult structures where single antioxidant compounds can exist in different form: soluble and insoluble. Consequently, it is significant to investigate antioxidant activity of food after in vitro digestion process (Gawlik-Dziki et al 2009;Chandrasekara and Shahidi 2012;Li et al 2014). However, linked polyphenols are most likely disengaged later in the colon after fermentation.…”
Section: Effect Of Soluble and Insoluble Fraction After Gastrointestimentioning
confidence: 99%
See 1 more Smart Citation
“…Yang et al [20] reported a similar observation in soybean broth and fermented soybean broth. Meanwhile, Xiao et al [21] found that fermented soy whey extracts showed significantly higher (P < 0.05) hydroxyl radical scavenging activity at concentrations of 0.08-0.24 mg/ml (freeze-dried extracts were dissolved in 80 % ethanol and diluted to various concentrations) because of higher amounts of phenolics [46]. In this study, we considered the higher hydroxyl radical scavenging ability of FPM resulting from the increase of peanut oligopeptides according to the findings of Zheng et al [22].…”
Section: In Fpmmentioning
confidence: 99%
“…Compared to polished Paddy rice, millets release lesser percentage of glucose over a longer period of time. Hence consumption of millets reduces risk of heart disease, protects from diabetes, improves digestive system, lowers the risk of cancer, increases immunity in respiratory health, and protective against several degenerative diseases such as metabolic syndrome and Parkinson's disease (Manach et al, 2005;Scalbert et al, 2005;Chandrasekara and Shahidi, 2012).…”
Section: Introductionmentioning
confidence: 99%